Current strength training practices within sprint kayaking - Crispin, C.; Del Vecchio, L. (Journal of Australian Strength and Conditioning, 2021)
Kayaking individual is an Olympic and individual team-based sport. However, there is a paucity of strength and conditioning (S&C) guidelines to support improvements in kayaking performance which aligns to the long-term athlete model. The purpose of this article is to describe the current strength training practices used in Australian sprint kayaking. The specificity of kayaking movement patterns is discussed in relation to exercise selections which are influenced by technique and verbal cueing. S&C guidelines and programming examples are provided for senior sprint kayakers. For example, the pull-up, bench press, bench pull and single arm row are key exercise selections because of their positive transfer to sprint kayaking performance. Expected strength benchmarks for these exercises for Male and Female athletes include: 3RM chin up >130-120% of body mass (BM); 3RM bench press >110-90% of BM; 3RM bench pull >110-100% of BM. Across the kayaking season, there are four phases of training: (1) the transition phase (TP), (2) the general preparation phase (GPP), (3) the specific preparation phase (SPP) and (4) the competition phase (CP). Athletes commence with two weekly S&C sessions in the GPP phase to build a strength base and work capacity. To further develop work capacity and strength four weekly S&C sessions are performed in the SPP. Finally, in the CP three weekly S&C sessions are performed, as the emphasis of training shifts towards maximal strength and power. Recommendations provided in this article may assist S&C coaches develop conditioning programs that enhance sprint kayaking performance.